VILLAGE POTENTIAL DEVELOPMENT STRATEGY BASED ON VILLAGE DEVELOPMENT INDEX (IDM) IN DUSUN BARU 1 VILLAGE, CENTRAL BENGKULU REGENCY - Efni; Mulyasari, Gita; Khairani, Lathifah; Saleh, Yopi (Universitas Veteran Bangun Nusantara, 2025)
Dusun Baru I Village, located in Pondok Kubang District, Central Bengkulu Regency, faced several challenges in its development. This study aimed to formulate a development strategy for Dusun Baru I Village based on the Village Development Index (IDM) and determine the village's position in the SWOT quadrant based on internal and external factors. Dusun Baru I Village encountered limited access to capital and a low utilization of local potential. This research employed a qualitative descriptive method, which aimed to analyze objects, conditions, human groups, or other phenomena in their natural state without experimental intervention. Data collection techniques included interviews, documentation, and questionnaires. The results of the IDM analysis indicated that Dusun Baru I Village had a score of 0.7857, categorizing it as an advanced village. IDM consisted of three indexes, and in this study, the environmental resilience index had the highest score. This finding suggested that Dusun Baru I Village had a well-managed environmental system with minimal disaster risks that could hinder village development. Meanwhile, the social resilience index showed that the social aspect of this village was already strong. This reflected a high level of education, adequate healthcare, and well-preserved cultural and social diversity, which contributed to a stable social condition that supported village development. However, the economic resilience index indicated that the village’s economic aspect remained a major challenge. The SWOT analysis placed this village in Quadrant II, which suggested the need for a diversification strategy to address greater external threats than the available opportunities. The proposed alternative strategies included utilizing land for public facilities, strengthening the village transportation system to support agricultural product distribution, and optimizing digital technology for micro-business marketing and disaster response information systems. Keywords: developing village indeks, development strategy, SWOT